Depression, anxiety, stress, and motivation over the course of smoking cessation treatment - Pawlina, Maritza Muzzi Cardozo; Rondina, Regina de Cássia [UNESP]; Espinosa, Mariano Martinez; Botelho, Clóvis (FapUNIFESP (SciELO), 2015)
Objective: To evaluate changes in the levels of patient anxiety, depression, motivation, and stress over the course of smoking cessation treatment. Methods: This cohort study involved patients enrolled in a smoking cessation program in Cuiabá, Brazil. We selected patients who completed the program in six months or less (n = 142). Patient evaluations were conducted at enrollment (evaluation 1 [E1]); after 45 days of treatment with medication and cognitive-behavioral therapy (E2); and at the end of the six-month study period (E3). Patients were evaluated with a standardized questionnaire (to collect sociodemographic data and determine smoking status), as well as with the University of Rhode Island Change Assessment scale, Beck Anxiety Inventory, Beck Depression Inventory, and Lipp Inventory of Stress Symptoms for Adults. The data were analyzed with the nonparametric Wilcoxon test for paired comparisons. To compare treatment success (smoking cessation) with treatment failure, the test for two proportions was used. Results: Among the 142 patients evaluated, there were improvements, in terms of the levels of anxiety, depression, motivation, and stress, between E1 and E2, as well as between E1 and E3. In addition, treatment success correlated significantly with the levels of motivation and anxiety throughout the study period, whereas it correlated significantly with the level of depression only at E2 and E3. Conclusions: We conclude that there are in fact changes in the levels of patient anxiety, depression, motivation, and stress over the course of smoking cessation treatment. Those changes appear to be more pronounced in patients in whom the treatment succeeded.
Keywords: Anxiety; Cognitive therapy; Depression; Motivation; Smoking cessation